KURIKULUM DAN TRADISI BELAJAR PADA SISTEM PENDIDIKAN ISLAM ABAD KE-20 - Abdurrahmansyah Abdurrahmansyah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2019)
This study aims to describe the curriculum and learning tradition developed by scholars in South Sumatra in the 20th century. The significance of this research is in addition to exploring the treasures of local Islamic education, it is also deemed necessary to look at the pattern of continuity and the model of continuity of the design of the Islamic education curriculum in the twentieth century with the traditions of Islamic education in the past. By using a descriptive qualitative research approach through optimizing documentary data searches, interviews, and observations of data sources that can still be traced in the form of works by 20th century clerical figures, relics in the form of pesantren and madrasa, as well as family and close relatives of the characters, which allows research accurately reveals the main problems of research. Through qualitative data analysis, this study presents important findings.First, 20th-century South Sumatra scholars represented by K.H. Anwar and K.H. Muhammad Zen Syukri has perpetuated the mainstream design of the curriculum of classical Islamic education with an emphasis on teaching the content of the fields of study of Aqidah, Islamic law, History, Sufism/Tasawuf, and Arabic. Curriculum innovation is carried out at the level of modification of the material presentation model through the writing of reference textbooks which are summarized from the main books in the classical education curriculum. Second, the learning traditions of students and local Muslims still maintain traditional learning models in the form of sorogan and bandongan besides adopting a modern classical education model. The local learning tradition in the form of majelistaklim and cawisan still seems to be maintained in the case of Islamic teaching in the local moslemcommunity.